Metabolism of Sodium Pentosan Polysulphate in Man Measured by a New Competitive Binding Assay for Sulphated Polysaccharides – Comparison with Effects Upon Anticoagulant Activity, Lipolysis and Platelet α-Granule Proteins - MacGregor, I R; Dawes, J; Pepper, D S; Prowse, C V; Stocks, J (Thrombosis and Haemostasis, 1985)
Three human volunteers were injected with a range of doses of pentosan polysulphate, SP54, i.v. or s.c. A competitive binding assay (CBA) for sulphated polysaccharides was used to detect circulating SP54 after doses as low as 1 mg i.v. and a linear relationship was observed between the peak plasma concentration of SP54 measured by CBA and the administered dose. A comparison was made between the clearance of SP54 measured by CBA and its anticoagulant and lipolytic activities. SP54 was detectable by CBA after doses which caused no alteration in activated partial thromboplastin time (APTT) or anti-factor Xa activity but after which a small increase of lipase activity was measurable. After SP54 at 10 mg i.v. or 100 mg s.c. anti-factor Xa activity was 4-6 times greater than would be expected from the in vitro activity of the concentrations of SP54 measured by CBA. Like heparin and other heparin analogues, SP54 caused an increase in plasma concentrations of platelet factor 4 (PF4) without a concomitant rise in p-thromboglobulin (β-TG).It is concluded that the newly developed CBA will provide a more sensitive means than conventional bioassays for the determination of plasma concentrations of SP54.
Keywords: Competitive binding assay; Anticoagulant; Lipase; Platelet proteins; Sulphated polysaccharides; Pentosan polysulphate